2021
DOI: 10.14740/cr1319
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes in Immune Checkpoint Inhibitor Therapy-Associated Myocarditis

Abstract: Immune checkpoint inhibitor (ICI) therapy has played an important role in the treatment of several groups of cancers. Although a life prolonging treatment, many side effects have been shown with ICI therapy. This study looked at individual level clinical characteristics and outcomes with ICI therapy in patients who developed ICI-related myocarditis. A comprehensive review of the National Library of Medicine PubMed database was performed. Inclusion criteria were all studies that were composed of case reports an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Previous studies have consistently demonstrated that anti‐PD‐1 and anti‐PD‐L1 antibodies cause various adverse effects 17–19 . The main cardiotoxicity associated with anti‐PD‐1/anti‐PD‐L1 antibodies is myocarditis 20–23 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have consistently demonstrated that anti‐PD‐1 and anti‐PD‐L1 antibodies cause various adverse effects 17–19 . The main cardiotoxicity associated with anti‐PD‐1/anti‐PD‐L1 antibodies is myocarditis 20–23 …”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 , 19 The main cardiotoxicity associated with anti‐PD‐1/anti‐PD‐L1 antibodies is myocarditis. 20 , 21 , 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myocarditis exhibited a wide spectrum of clinical manifestations, with the vast majority presenting with nonspecific systemic symptoms such as gastroenteritis, myalgia, fever, or respiratory symptoms [ 10 ], in addition to the possibility of arrhythmias, palpitations, and exertional dyspnea [ 11 , 12 ] in patients with myocarditis. This varies widely in clinical presentation leading to the diagnosis being sometimes difficult to establish, and numerous therapies for myocarditis have not demonstrated survival benefits [ 13 ]. Therefore, a lot of research is still needed to deeply analyze the underlying mechanism of myocarditis infiltration to provide the basis for the diagnosis and treatment of myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…ICI-related myocarditis is associated with a high reported mortality [4]. A comprehensive review of ICI therapy and myocarditis has found that ICI therapy-related myocarditis occurs at an average age of 68 years, and the characteristics of the patients include higher incidence in men and pretreatment cardiac history of hypertension [5]. Especially, ICI therapy with nivolumab, an anti-programmed death protein 1 (PD-1) monoclonal antibody, had mortality in 51.9% [5].…”
Section: Immune Checkpoint Inhibitors (Icis) In Cancer Treatment and ...mentioning
confidence: 99%